The influences of early history on multicultural Melaka - DEVINDER RAJ (Devinder Raj, 2021)
This is not an ordinary guide to Melaka. This book weaves together history, cultures, architecture and cuisine to tell a more multifaceted story of Melaka, once a great trading port fought over by various colonial powers, resulting in a rich heritage that is still salient today, resulting in a multicultural city reflecting its cosmopolitan journey over the centuries. Journey along the old streets of Melaka and past its ruins, where its rich history, reflecting hundreds of years of Asian and European influence, remains alive and evolving to this day.